2010
DOI: 10.1002/anie.200905102
|View full text |Cite
|
Sign up to set email alerts
|

Drug Design for G‐Protein‐Coupled Receptors by a Ligand‐Based NMR Method

Abstract: More than 50 % of all drug targets are membrane proteins. [1] Recent progress in membrane protein crystallography has made a few of these targets amenable to established structurebased design methods.[2] However, crystallization of a membrane protein target remains a challenge, and medicinal chemists must rely on ligand-based design approaches for the targets that do not crystallize. These approaches can benefit from the knowledge of the bioactive conformation of the ligand conformation and the relative orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…163 By the use of an NMR-based method for GPCR screening, Bartoschek and co-workers were able to identify novel submicromolar FFA1 agonists such as 9. 164 Using free fatty acids as the starting point and inspiration from the early thiazolidinediones in the design of small druglike free fatty acid-mimicking compounds, Christiansen et al identified a phenoxyacetic acid hit containing a central alkyne that was optimized to the potent and selective TUG-424 (10), which was confirmed to enhance insulin secretion at high but not low glucose levels in a FFA1-dependent manner. 165 This compound, however, displayed lower than ideal in vitro metabolic stability and short plasma half-life, suspected to reflect metabolism of the ortho-methyl group and/or betaoxidation.…”
Section: Synthetic Ligands For Ffa1mentioning
confidence: 99%
“…163 By the use of an NMR-based method for GPCR screening, Bartoschek and co-workers were able to identify novel submicromolar FFA1 agonists such as 9. 164 Using free fatty acids as the starting point and inspiration from the early thiazolidinediones in the design of small druglike free fatty acid-mimicking compounds, Christiansen et al identified a phenoxyacetic acid hit containing a central alkyne that was optimized to the potent and selective TUG-424 (10), which was confirmed to enhance insulin secretion at high but not low glucose levels in a FFA1-dependent manner. 165 This compound, however, displayed lower than ideal in vitro metabolic stability and short plasma half-life, suspected to reflect metabolism of the ortho-methyl group and/or betaoxidation.…”
Section: Synthetic Ligands For Ffa1mentioning
confidence: 99%
“…Two other binding techniques have developed enhanced specificity for the ligand–receptor interaction under study. Bartoschek et al (2010) generated FFAR1 binding data from saturation transfer difference 1 H nuclear magnetic resonance (NMR) measurements, in which NMR spectra are obtained only when ligands bind a macromolecular complex, such as a receptor protein. They showed that this method allowed estimation of agonist IC 50 values from competition binding experiments, which displayed close correspondence with functional potencies.…”
Section: Experimental Challenges In Understanding Long Chain Ffa Recementioning
confidence: 99%
“…The ligand-based methods, which typically involve comparison of the NMR parameters of a mixture of compounds in the presence and absence of the protein molecules, rely on the exchange-mediated transfer of bound state information to the free state. This biases ligand-based methods towards identification of weakly binding ligands (rapid exchange), but it does render the molecular weight of the protein molecule largely irrelevant, and indeed the approach has been applied to the ribosome, to receptors in membranes and to whole cells [64][65][66][67][68][69][70]. Competition experiments can be used to extend the range of the relaxation approach to tighter binding ligands, including those which are not in fast exchange.…”
Section: Detecting Binding -Nmr Screeningmentioning
confidence: 99%